Total Parenteral Nutrition Successfully Treating Black Esophagus Secondary to Hypovolemic Shock - Tony S. Brar; Richard Helton; Zareen Zaidi (Case Reports in Gastrointestinal Medicine)
We present a patient who developed black esophagus secondary to hypovolemic shock and was placed on total parenteral nutrition for three weeks after hospital discharge. The area of interest is the multimodal approach used in treatment of this noncompliant patient. Even with a high mortality rate, this case illustrates a successful outcome of a patient who responded to appropriate immediate therapy resulting in complete resolution of the necrosis with no further development of complications.